Retinoic Acid Excess Impairs Amelogenesis Inducing Enamel Defects - Morkmued, Supawich; Laugel-Haushalter, Virginie; Mathieu, Eric; Schuhbaur, Brigitte; Hemmerlé, Joseph; Dollé, Pascal; Bloch-Zupan, Agnès; Niederreither, Karen (Frontiers in Physiology, 2017)
Abnormalities of enamel matrix proteins deposition, mineralization, or degradation during tooth development are responsible for a spectrum of either genetic diseases termed Amelogenesis imperfecta or acquired enamel defects. To assess if environmental/nutritional factors can exacerbate enamel defects, we investigated the role of the active form of vitamin A, retinoic acid (RA). Robust expression of RA-degrading enzymes Cyp26b1 and Cyp26c1 in developing murine teeth suggested RA excess would reduce tooth hard tissue mineralization, adversely affecting enamel. We employed a protocol where RA was supplied to pregnant mice as a food supplement, at a concentration estimated to result in moderate elevations in serum RA levels. This supplementation led to severe enamel defects in adult mice born from pregnant dams, with most severe alterations observed for treatments from embryonic day (E)12.5 to E16.5. We identified the enamel matrix proteins enamelin (Enam), ameloblastin (Ambn), and odontogenic ameloblast-associated protein (Odam) as target genes affected by excess RA, exhibiting mRNA reductions of over 20 fold in lower incisors at E16.5. RA treatments also affected bone formation, reducing mineralization. Accordingly, craniofacial ossification was drastically reduced after two days of treatment (E14.5). Massive RNA-sequencing (RNA-seq) was performed on E14.5 and E16.5 lower incisors. Reductions in Runx2 (a key transcriptional regulator of bone and enamel differentiation) and its targets were observed at E14.5 in RA-exposed embryos. RNA-seq analysis further indicated that bone growth factors, extracellular matrix, and calcium homeostasis were perturbed. Genes mutated in human Amelogenesis imperfecta (ENAM, AMBN, AMELX, AMTN, KLK4) were reduced in expression at E16.5. Our observations support a model in which elevated RA signaling at fetal stages affects dental cell lineages. Thereafter enamel protein production is impaired, leading to permanent enamel alterations.